Konflik Komunikasi Kelompok Pecinta Klub Sepak Bola Persija (The Jakmania) di Kota Medan - Valeri, Rendy Grimaldi; Ritonga, Syafruddin; Novri, Novri (Universitas Medan Area, 2024)
This paper reveals the origins of Communication Conflict in the Persija Football Club Lovers Group (The Jakmania) in Medan City and efforts to overcome it. Referring to relevant theories, data is obtained from various sources such as books, previous research, and internet media, then analyzed qualitatively. The study concluded that communication conflicts among members of The Jakmania Medan stemmed from negative comments against Persija on social media, triggering revenge intentions among them. Disagreements occur between members who support revenge and those who don't, and can even trigger physical confrontation during arguments. The role of the group leader in resolving this conflict involves mediation and sanctioning, such as the revocation of the Member Identity Card (KTA) and legal sanctions. These steps are expected to restore harmony and overcome internal conflicts within The Jakmania Medan community.